Escaping from Adversity in Novel A Million Little Pieces by James Frey (2003) - Winda Rawilta Putri; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2023)
The purpose of this analysis is to expose the issue of escaping adversity in the Novel A Million Little Pieces by James Frey (2003). The issue of escaping adversity refers to the ways the character when the character wants to get out of drug addiction. This analysis is text-based interpretation based on the theory life instinct by Sigmund Freud. This analysis uses fictional devices such as character, plot (conflict) and setting that contribute in revealing the issue. The result of the study reveals the man escapes his adversity. It can be seen through his behaviour such as create new life, cooperate with others, and his pro-social action.